Benefits from adopting technologies for the hotel’s supply chain management - Vesna Milovanović; Daniel Chong Ka Leong; Mihailo Paunović (Mенаџмент у хотелијерству и туризму, 2022)
Information and communication technologies (ICTs) have a significant role in contemporary business activities, helping companies to improve quality, efficiency, flexibility and learning capacity, to reduce costs, and finally, to achieve competitive advantage. The aim of this paper is to examine the extent of implementation, as well as the benefits of ICTs used for the hotel supply chain management (SCM). A survey has been conducted involving 40 hotels in Serbia categorized as four- and five-star. The results reveal modest to scanty adoption of SCM-related ICTs among hotels in Serbia. Hotel managers find ICTs they use as very beneficial regarding: (1) more efficient and faster guest attraction, (2) more efficient communication with suppliers, (3) increased speed, (4) increased flexibility, (5) reduced costs and (6) improved guest services. It was also found that the size and affiliation of hotels do not impact the benefits, while the category is positively associated with benefits from using the SCM technologies.